1974
DOI: 10.2466/pms.1974.38.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Psychological Primary Colors on GSR, Heart Rate and Respiration Rate

Abstract: Judges selected from ISCC-NBS patches those colors which were most representative of red, yellow, green, and blue. These colors were presented for 1 min. each with GSR, heart rate, and respiration being recorded. There was a significant color effect on GSR but not on the other measures. Red was significantly more arousing than blue or yellow and green more than blue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(135 citation statements)
references
References 9 publications
4
120
2
4
Order By: Relevance
“…19 A similar study monitoring physiological variables showed greater increases in heart rate and respiratory rate with red and yellow than with blue and green. 20 We conclude that colour may be one of the reasons why patients prefer paintings depicting nature scenes, since these are often dominated by blue and green.…”
Section: Effects Of Colours On Emotionsmentioning
confidence: 99%
“…19 A similar study monitoring physiological variables showed greater increases in heart rate and respiratory rate with red and yellow than with blue and green. 20 We conclude that colour may be one of the reasons why patients prefer paintings depicting nature scenes, since these are often dominated by blue and green.…”
Section: Effects Of Colours On Emotionsmentioning
confidence: 99%
“…The secretion of melatonin is strongly associated with the circadian rhythm of core temperature. Concerning the nonvisual pathway, the literature has demonstrated the effect of light exposure on the autonomic nervous system (e.g., Jacobs and Hustmyer, 1974;Kobayashi and Sato, 1992;Jin et al, 2007), as well as the thermal regulation system (e.g., Scheer et al, 2005), showing the interaction of environmental light and the SCN in body temperature regulation. Since the pineal body is located near the hypothalamus, which regulates core temperature, reciprocal or one-sided afferent information may be incorporated into the body temperature regulation system, and the results suggest that afferent information via the nonvisual pathway on light exposure may play a significant role of reducing the autonomic control of core temperature.…”
Section: Effect Of Light Conditions On the Cizmentioning
confidence: 99%
“…Many studies e.g. 17,18 have shown that blue and green hues tend to elicit a state of relaxation, whereas yellow and red hues elicit more excitement. Consequently, it would be expected that the hue of the blue/green website would invoke a more relaxed response than the red website.…”
Section: Colourmentioning
confidence: 99%